PERBEDAAN KOMUNIKASI INTERPERSONAL ANTARA REMAJA BROKEN HOME DAN REMAJA BUKAN BROKEN HOME DI SMP AL WASHLIYAH 20 MEDAN - Ramadhani , Sri; Sari, Inggrit Puspita; Sinarsi; Hura, Glori Debora; Januario, Tondy Ridho (JURNAL PSYCHOMUTIARA, 2024)
This research aimed to investigate the differences in interpersonal communication between adolescents from broken homes and those from non-broken homes at SMP Al Washliyah 20 Medan. Interpersonal communication is crucial in families for building harmony and reciprocity. However, in broken homes, interpersonal communication between parents and children tends to be ineffective due to parental busyness, causing children to become withdrawn. In contrast, in non-broken homes, interpersonal communication is more effective, and children are more open. This quantitative study employed a nonprobability sampling technique involving 60 students. The data analysis using the Mann-Whitney U test showed a significance of 0.000 < 0.05, indicating that the hypothesis was accepted and a significant difference existed in interpersonal communication between adolescents from broken homes and those from non-broken homes.